Vitrocerâmicas do sistema Li2O - Al2O3 - SiO2 (LAS) via sinterização com cristalização concorrente - Soares, Viviane Oliveira (2007)
LAS (Li2O-Al2O3-SiO2) glasses have been often used to produce glass- ceramics with near zero thermal expansion coefficient. These glass-ceramics are very important for applications that require high thermal shock resistance. However, they are still produced by traditional techniques, such as melting and forming followed by internal nucleation (induced by the addition of catalysts) and crystal growth in the volume of monolithic glass pieces. An alternative route for the production of glass-ceramics is via sintering of catalyst-free glass particles with controlled surface crystallization. The purpose of the present work was to determine the appropriate compositions and sintering conditions to produce dense LAS glass-ceramics having almost null porosity. Three compositions were analyzed to achieve near zero thermal expansion coefficient. The precursor glasses were analyzed by thermal analysis, and the glassceramics were analyzed by X-ray diffraction, optical microscopy and electron microscopy. Dense glass-ceramics were obtained with porosity below 1.5%. The results show that reduction of crystallization by an ion exchange promotes sintering. However, the high amount of vitreous phase present in these samples increases the thermal expansion coefficient. At least for one composition we obtained a glass-ceramic having a porosity of 1.4% and a thermal expansion coefficient of 0.5 x 10 -6 °C-1, a value similar to that of vitreous silica.